STRATEGI PENGEMBANGAN PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM DI SMA BUSTANUL ULUM ANAK TUHA - Mahmud Hafiz; Supriyatmoko; Ilham Ridho Rahman (STIT Bustanul 'Ulum Lampung Tengah, 2025)
This study investigates the strategic management of professional development for Islamic Religious Education (IRE) teachers at SMA Bustanul Ulum Anak Tuha, focusing on enhancing their pedagogical quality and character-building roles. In the broader context of educational reform and professional standards, the research aims to explore how schools empower IRE teachers to become professional educators who also act as spiritual and moral role models. Utilizing a qualitative descriptive approach and field research method, the study involved observations, interviews, and documentation to collect in-depth data. The findings reveal several strategies: effective classroom management, integration of instructional media, utilization of school facilities, active implementation of the Guru Penggerak (Teacher Mobilizer) program, creative adaptation to the Merdeka Curriculum, and a strong emphasis on character education. Teachers demonstrated high levels of commitment to student-centered learning, technological integration, and value-based instruction, despite facing challenges such as limited instructional time and diverse student backgrounds. The study concludes that professional development of IRE teachers involves not only pedagogical competence but also leadership, creativity, and resilience. These strategies contribute significantly to student motivation, religious character, and learning outcomes. The research highlights the importance of continuous professional support and school leadership in sustaining teacher innovation and effectiveness in religious education.